Impact of type 2 diabetes mellitus on hematoma expansion and clinical outcomes in patients with spontaneous intracranial hematoma - Yang, Junhua; Wang, Sihui; Ji, Xiangtian; Sun, Yu; Feng, Jingyu; Liu, Bin; Yang, Jun (Frontiers in Surgery, 2025)
Background and purposeSpontaneous intracerebral hemorrhage (sICH) significantly affects patient outcomes. Diabetes mellitus (DM) is a common comorbidity associated with sICH; however, the influence of DM on hematoma expansion (HE) and clinical prognosis in sICH patients remains a subject of debate.MethodsThis multicenter retrospective study included sICH patients who visited the neurosurgery departments of eight hospitals between 1 January 2015 and 31 May 2021. These patients were followed up for 6 months post-sICH and divided into two groups: those with type 2 DM (DM group) and those with no diabetes mellitus (nDM group). The chi-square test, Mann–Whitney U test, and multivariate logistic regression analysis were employed to evaluate the impact of DM on HE and patient outcomes.ResultsA total of 1,453 patients were admitted to the eight hospitals between 1 January 2015 and 31 May 2021. A total of 1,134 sICH patients were ultimately included in this study for further analysis, based on the inclusion and exclusion criteria. Of these, 182 (16.0%) patients were assigned to the DM group, while 952 (84.0%) patients were assigned to the nDM group. In the intergroup comparison, significant differences were observed in terms of gender, age, smoking, hypertension, coronary heart disease, antiplatelet therapy, ventricular hematoma, and heterogeneous hematoma density. After adjusting for the above confounders, DM was found to significantly increase the incidence of HE (3.552, 95% CI: 2.342–5.387, p = 0.000). Similarly, DM significantly increased all-cause mortality at 1 month (1.965, 95% CI: 1.006–3.840, p = 0.048), 3 months (1.980, 95% CI: 1.071–3.662, p = 0.029), and 6 months (1.776, 95% CI: 1.034–3.050, p = 0.038) in sICH patients. However, DM did not worsen functional prognosis in patients with sICH at 1 month (1.363, 95% CI: 0.909–2.043, p = 0.134), 3 months (1.124, 95% CI: 0.746–1.692, p = 0.577), and 6 months (1.177, 95% CI: 0.789–1.754, p = 0.425), after adjusting for confounding factors.ConclusionDM is a risk factor for HE and all-cause mortality at 1, 3, and 6 months post-sICH. However, DM does not significantly worsen the functional prognosis of sICH patients at 1, 3, and 6 months.